Bamako Sounds : The Afropolitan Ethics of Malian Music - Skinner, Ryan Thomas (Book collections on Project MUSE., 2015)
Bamako Sounds tells the story of an African city, its people, their values, and their music. Centered on the music and musicians of Bamako, Mali's booming capital city, this book reveals a community of artists whose lives and works evince a complex world shaped by urban culture, postcolonialism, musical expression, religious identity, and intellectual property. Drawing on years of ethnographic research with classically trained players of the kora (a twenty-one-string West African harp) as well as more contemporary, hip-hop influenced musicians and producers, Ryan Thomas Skinner analyzes how Bamako artists balance social imperatives with personal interests and global imaginations. Whether performed live on stage, broadcast on the radio, or shared over the Internet, music is a privileged mode of expression that suffuses Bamako's urban soundscape. It animates professional projects, communicates cultural values, pronounces public piety, resounds in the marketplace, and quite literally performs the nation. Music, the artists who make it, and the audiences who interpret it thus represent a crucial means of articulating and disseminating the ethics and aesthetics of a varied and vital Afropolitanism, in Bamako and beyond.